Research of cross-tier cooperative transmission technology in heterogeneous network - GChen ZHAN; Xin SU; Wen-qing WANG; Jie ZENG; Yu-jun KUANG (Tongxin xuebao)
A cross-tier cooperative transmission strategy with cooperative precoding is used to reduce the intercell inter-ference in heterogeneous network, especially the interference in cell range expansion areas. The proposed cooperative strategy supports the cooperative transmission of Macro BS and low power BS at resource block level based on LTE-Advanced downlink transmission system. Simulation results indicate that the cooperative strategy based on hierar-chical cooperative framework provides more satisfactory system throughput gains compared with non-cooperative scheme and the existing eICIC technology under cell range expansion.